Alterações do sono, sintomas depressivos e mortalidade : estudo longitudinal de 400 pacientes em hemodiálise - Araujo, Sonia Maria Holanda Almeida (2010)
SPI and Hemodialysis. The study comprised two phases, first phase in a cross-sectional and prospectively over the next two years (2007-2009) to evaluate sleep disturbances, depressive symptoms and mortality in patients on hemodialysis (HD). Of the 400 patients studied 59% were men, mean age = 51.6 ± 15.5 in HD for 5.9 ± 5.5 years. Restless Leg Syndrome (RLS) present in 21.5% predominated in women (p <0.005), 55.8% had RLS impairment (International Restless Legs Syndrome (IRLS)> 15) and 44.2% mild symptoms. RLS patients had a reduction in hemoglobin (p <0.005) and tendency to hypoalbuminemia (p = 0.06). Poor quality of sleep (Sleep Quality Index in Pittsburgh, PSQI> 5) was more common in individuals with RLS were compared to those without RLS (69.8% vs 56.8%, p = 0.002). The risk of OSA was higher in patients with RLS (all cases p = 0.01 and RLS cases with moderate / severe, p = 0.007, respectively). Cases with SPI moderate / severe were associated with hypertension (p = 0.01) that remained after controlling for risk of OSA (p = 0.02). The shifts of dialysis were not related to sleep disorders or depression symptoms and other clinical and laboratory findings. Sleep disturbances and depressive symptoms in HD. We used the PSQI questionnaire, the Epworth Sleepiness Scale (ESS), the Berlin questionnaire, the BDI-II and Charlson Comorbidity Index (CCI). The independent risk factors associated with poor sleep quality (56.8%) were heart failure (OR = 1.99, p = 0.006), age (OR = 1.01, p = 0.009). The independent risk factors for depression (BDI-II> 16, 19.3%) were diabetes (OR = 2.96, p = 0.001), female gender (OR = 1.96, p = 0.007), and hypoalbuminemia (OR = 1.86, p = 0.024). Mortality. The multiple regression test showed that in both genders, increasing age and comorbidities were associated with mortality. In women, the comorbidity rates determined mortality (p<005). In men, hypoalbuminemia ((p=0.007), older age (p<005), parathyroid hormone (p=0.001) and reduced excessive daytime sleepiness (p=0.03) were associated with mortality. Conclusion. The prevalence of depression in HD patients is higher than the general population. Female gender, diabetes, heart failure, hypoalbuminemia and age are important conditions associated with depression in HD patients and are useful features to identify priority patients who may benefit from the treatment of depression after his screening. Women and individuals with anemia are at greater risk of SPI and SPI has proved important in this study by its association forms moderate / severe arterial hypertension, and depression and poor sleep quality. Benefits of treatment and a possible impact on these parameters must be evaluated. Somnolence excessive daytime sleepiness associated with cerebrovascular disease and anemia instigates the possibility that correction of anemia may improve sleepiness a known risk factor for CVD and mortality. The influence of different factors on mortality in men and women in these patients deserves to be explored.